Rabies Virus Exposure of Brazilian Free-ranging Wildlife from Municipalities without Clinical Cases in Humans or in Terrestrial Wildlife - Azevedo de Paula Antunes, Joao Marcelo; Demoner, Larissa de Castro; Andrade Cruvinel, Tatiana Morosini de; Kataoka, Ana Paula; Alves Martorelli, Luzia Fatima; Machado, Gustavo Puglia [UNESP]; Megid, Jane [UNESP] (Wildlife Disease Assoc, Inc, 2017)
Rabies is a zoonosis that causes thousands of animal and human deaths worldwide. Serological studies provide information concerning rabies virus circulation among animals and humans. We evaluated the circulation of the rabies virus in wildlife in nine municipalities of Sao Paulo State, Brazil. We took blood samples from 27 terrestrial animals of nine different mammalian species in locations without cases of rabies in human and wild terrestrial mammals. Sera were tested with the use of the rapid fluorescent focus inhibition test (RFFIT) for the detection of rabies virus-neutralizing antibodies (RVNA). The RFFIT was positive in 100% of the samples, with many (81.48%) showing protective titer levels (>0.5 IU/mL) with other samples (18.52%) showing titers representing exposure (<0.5 IU/mL). We report RVNA in novel species (e.g., Alouatta caraya and Tapyrus terrestris). Wild animals were exposed to rabies virus in municipalities without a history of human rabies cases, which demonstrated a need for research to understand the role of these animals in the circulation and transmission of the disease.
Keywords: Brazil; public health; viral circulation; wildlife; zoonosis